2002
DOI: 10.1016/s0378-4371(02)01074-9
|View full text |Cite
|
Sign up to set email alerts
|

How does water freeze inside carbon nanotubes?

Abstract: Phase behavior of quasi-one-dimensional water conÿned inside a carbon nanotube is studied in the thermodynamic space of temperature, pressure, and diameter of the cylindrical container. Four kinds of solid-like ordered structures-ice nanotubes-form spontaneously from liquid-like disordered phases at low temperatures. In the model system that comprises of TIP4P water molecules interacting with each other via short-range Lennard-Jones and long-range Coulomb site-site potentials under a periodic boundary conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 16 publications
9
89
0
Order By: Relevance
“…The first evidence for such transitions was again obtained from MD simulations combined with free-energy calculations: the simulations demonstrated that water inside a carbon nanotube freezes into four different forms of the ice nanotube, a class of quasi-one-dimensional crystalline ices. 17,18 The predicted formation of the ice nanotube was confirmed by experiments of Maniwa et al 19 The structure, dynamics, and thermodynamic properties of confined water depend on many factors such as confining geometry and physical and chemical properties of surfaces, and the effect of each factor is as yet little understood. Thus it is sensible to choose and study, among many possibilities, model systems with simpler geometries ͑e.g., slit and cylindrical pores͒ and simpler surfaces ͑e.g., structureless surfaces͒.…”
Section: Introductionmentioning
confidence: 87%
“…The first evidence for such transitions was again obtained from MD simulations combined with free-energy calculations: the simulations demonstrated that water inside a carbon nanotube freezes into four different forms of the ice nanotube, a class of quasi-one-dimensional crystalline ices. 17,18 The predicted formation of the ice nanotube was confirmed by experiments of Maniwa et al 19 The structure, dynamics, and thermodynamic properties of confined water depend on many factors such as confining geometry and physical and chemical properties of surfaces, and the effect of each factor is as yet little understood. Thus it is sensible to choose and study, among many possibilities, model systems with simpler geometries ͑e.g., slit and cylindrical pores͒ and simpler surfaces ͑e.g., structureless surfaces͒.…”
Section: Introductionmentioning
confidence: 87%
“…All MD simulations were performed by using a constant temperature/constant axial pressure ensemble (5,6). Periodic boundary conditions were applied only in the axial (z) direction.…”
Section: Simulationmentioning
confidence: 99%
“…20 Divide the hollow space into n w subsystems, each of which is multiply occupied by guests, and take into account indistinguishability o f the same kind of guest molecules. Then, the relevant grandcanonical partition function is given as = e x p ( ; n w A 0 w ) nm X ng=0 expf (n g g ; f ng )g] nw (2) where f ng is the free energy of occupancy by n g guest molecules of the mass m in a subsystem. The average guest numberis calculated as < N g >= @ ln @( g ) = n w P ng=1 n g expf (n g g ; f ng )g] P ng=0 expf (n g g ; f ng )g] :…”
Section: B Approximate Evaluation Of the Occupancymentioning
confidence: 99%
“…However, recent theoretical studies on water con ned in the carbon nanotube and the experimental studies followed have demonstrated that the con ned water freezes into crystalline structures that have n e v er been found in the bulk counterpart and exhibits continuous and discontinuous freezing transitions. 1,2 Computer simulation studies revealed that the structure of solid water in the zigzag (`, 0) single-walled carbon nanotube (SWCN) (with`=13, 14, ..., or 17) is quite di erent from the bulk ice structure it is a one-dimensional array o f n-gonal \rings", called an ice nanotube. 1,2 As in the ordinary ice, every water molecule in the carbon nanotube is hydrogen-bonded to its four neighbors in the solid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation